PENERAPAN MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 42 PEKANBARU - Sinaga, Mardiana; Alpusari, Mahmud; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to improve science learning outcomes with Inquiry learning model in the students of VA SDN 42 Pekanbaru. This study is classroom action research (CAR), with the subject of research was student class VA SDN 42 Pekanbaru.. The result of research showed that science learning through model Inquiry learning can improve science learning outcomes. This can be seen from : (1)teacher activity increases from percentage of teacher activity in the first cycle of 62,50% (good category) , in the second cycles of 87,50% (very good category); (2) students learning activities of increase in each cycle. Student learning activities increased from the percentage of student learning activities in the first cycle of 66,67% (good category) , on the second cycles of 91,67% (very good category);(3)student learning outcomes increase from average value before action equal to 67,69 with completness 51,28% (unfinished), increase in cycles I equal to 10,73% with a value 77,69 (high category), and in cycle II increased by 16,67% with value 84,36 (high category),with overall improvement for the learning result of this science is 26,67%.Key words : Inquiry Learning, learning outcomes, implementation of learning.